Tandem duplication in ermC translational attenuator of the macrolide-lincosamide-streptogramin B resistance plasmid pSES6 from Staphylococcus equorum. - Lodder, G (1996)
A tandem duplication of 23 bp in the ermC gene translational attenuator of plasmid pSES6 from Staphylococcus equorum which mediated constitutive resistance to macrolide-lincosamide-streptogramin B antibiotics was identified. This duplication included the ribosome binding site for the ermC gene as well as the first 5 bp of the ermC coding sequence. It was postulated that this sequence duplication affects the possible RNA conformations so that the ribosome binding site for ErmC synthesis is readily accessible to the ribosomes and thus constitutive expression of the ermC gene occurs.